COVID-19 a funkcjonowanie polskiego więziennictwa - Niełaczna, Maria (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
The aim of the article is to explain the low incidence of the COVID-19 phenomenon in Polish prisons. My aim is to answer three questions: was the Polish prison system ready to respond to the threats posed by COVID-19, what actions did it take and with what eﬀect. I found that during the COVID-19 epidemic — despite serious chronic systemic problems in the Polish prison system — the statistics indicated that of the 24 people infected with the virus, none have died. During this period, 33,195 new prisoners were admitted to Polish prisons. As for the statistics of freedom cases, the result was extremely low.
Keywords: więzienie; więźniowie; zdrowie w więzieniu; COVID-19; prawo do zdrowia ochrona